2015
DOI: 10.1007/s11295-015-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of quantitative genetics of gum arabic production complicated by variability in ploidy level of Acacia senegal (L.) Willd

Abstract: Gum arabic is an important international commodity produced by trees of Acacia senegal across Sahelian Africa, but documented results of breeding activities are limited. The objective of this study was to provide reliable estimates of quantitative genetic parameters in order to shed light on the breeding potential for improvement of gum yield and quality. For this purpose, we measured growth on 617 offspring from 60 open-pollinated trees after 18 years, and gum yield and quality based on two seasons, 18 and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…All 634 living trees in the field trial were genotyped with 8 polymorphic microsatellite markers (SSR) as described in Diallo et al (2015) . By comparing the flow cytometry results with the SSR markers for the 59 mature trees, we concluded that polyploids could always be separated from diploids by the presence of more than two alleles per locus in at least 1 of the 8 loci (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 634 living trees in the field trial were genotyped with 8 polymorphic microsatellite markers (SSR) as described in Diallo et al (2015) . By comparing the flow cytometry results with the SSR markers for the 59 mature trees, we concluded that polyploids could always be separated from diploids by the presence of more than two alleles per locus in at least 1 of the 8 loci (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Investigating a progeny trial with mature A. senegal , we discovered that the trees had mixed ploidy levels ( Diallo et al, 2015 ). As the trial was established with the purpose of breeding for increased gum production, the trees were planted in an experimental design and thus represent a unique possibility for studying the long-term performance of di- and polyploid trees.…”
Section: Introductionmentioning
confidence: 99%
“…Gum arabic fractionated by hydrophobic affinity chromatography detects a broad spectrum of arabinogalactans, arabinogalactan-proteins, and/or glycoproteins (Osman et al, 1993;Renard et al, 2006). Diallo et al (2015) reported that provenances as well as certain families of polyploids had a different nitrogen content in their gum arabic. However, provenances, families, or plant ploidy levels appeared to have only a minor effect on carbon content.…”
Section: Senegalia Senegal Gum Productionmentioning
confidence: 99%
“…Thus, like nitrogen content, protein quantity in S. senegal gum arabic changes with environmental conditions, but it may also be affected by ploidy level. Research by Diallo et al (2015) showed that for both diploid and polyploidy trees, plant growth and gum yield/quality differed among ploidy levels, and in populations and progenies.…”
Section: Senegalia Senegal Gum Productionmentioning
confidence: 99%
“…The current study stresses the importance of using DNA markers in assessing the mating system and the relationship within and among families as part of the estimation of quantitative genetic parameters to support breeding activities in A. senegal. [2]. In genetic improvement, it is essential to estimate heritability and phenotypic variability for different traits to make successful decisions in breeding strategies.…”
Section: Introductionmentioning
confidence: 99%